HUBUNGAN ANTARA OPTIMISME DAN DUKUNGAN SOSIAL DENGAN COPING STRESS PADA MAHASISWA KEPERAWATAN YANG SEDANG MENYUSUN SKRIPSI DI STIKES MUHAMMADIYAH SAMARINDA - ., Rizki Ramadhani (MOTIVASI, 2014)
This study aims to determine whether there is a relationship between optimism and social support with copingstress . So there are three relationships that will be investigated in this study , namely : 1 ) Optimism withCoping Stress ; 2 ) Social Support with Coping Stress ; 3 ) Optimism and Social Support with Coping Stress.Research applied to nursing students of STIKES Muhammadiyah Samarinda . The subjects in this study were81 nursing students who are writing their thesis on STIKES Muhammadiyah Samarinda . Sampling in thisstudy using saturation sampling technique in which all population are used as the sample because thepopulation is relatively small. Data analysis techniques used is multiple regression analysis . The resultsshowed that there is a positive and significant relationship between optimism with coping stress with beta =0.726 , t = 6235 , R ² = 0.483 and p = 0.000 . There was no relationship between social support with copingstress due to the value of beta = 0197 , t = 2307 , R ² = 0.226 and p = 0.710 . Then on optimism and socialsupport with coping stress there is significant correlation with F = 36 530 , R ² = 0.484 , and p = 0.000 .